The VITA Project: Prothrombin G20210A Mutation and Venous Thromboembolism in the General Population - Tosetto, Alberto; Missiaglia, Edoardo; Frezzato, Maurizio; Rodeghiero, Francesco (Thrombosis and Haemostasis, 1999)
Recently a new identified genetic variant in the 3’-untranslated region of the prothrombin gene (G20210A allele) associated with increased plasma prothrombin levels has been linked to an increased risk of venous thromboembolism (VTE). Most of our knowledge on the G20210A allele as a risk factor for VTE derives from a population-based case-control study and from studies on selected series of VTE patients. To determine the importance of the G20210A allele as a causative risk factor for VTE in the general population, we analyzed the cross-sectional data of the Vicenza Thrombophilia and Atherosclerosis (VITA) Project. One hundred sixteen cases of VTE, ascertained in a random fashion within the general population aged 18-65, were age and sex-matched with 232 healthy subjects. Heterozygosity for the G20210A allele was present in 4.3% of VTE cases and in 3.4% of controls, indicating a marginal increase of VTE risk in carriers of the allele (odds ratio: 1.26; 95% CI 0.4-3.9). However, the VTE risk was substantially higher in subjects with idiopathic VTE before age 45 or with recurrent, idiopathic VTE (odds ratio: 2.8; 95% CI 0.6-13.8) or in subjects with a family history of VTE (odds ratio: 7.6; 95% CI 1.8-32.8). Accordingly, our results suggest that the G20210A allele associates with VTE only in selected cases, and that screening for this genetic variant is not warranted for all patients with VTE.
Keywords: Prothrombin; venous thromboembolism; thrombophilia; epidemiological studies; genetics